2020
DOI: 10.1176/appi.ps.201900246
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Job Stressors Associated With Turnover and Turnover Intention Among Community Mental Health Providers

Abstract: This study aimed to examine the provider characteristics and job stressors that are related to turnover intention and actual turnover among community mental health providers. Methods: Secondary analyses were conducted with data collected from 186 community mental health providers from two agencies. Self-reported provider characteristics, job stressors, and turnover intention data were collected with the baseline survey, and actual turnover data were obtained from the agencies 12 months later. Bivariate analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Mattering was also reported to be the protective factor against depression symptoms and suicide ideation among young adults [22], [23]. The decision to involve mattering as our main predictor in this current study is also confirmed because it has been established that employees with higher levels of mattering tend to have higher job satisfaction, perceive lower job stress, as well as perceive higher work-life balance [4], [24], [25] that will lead to lower turnover intention [26]. Our second choice as the predictor of turnover intention was the organizational commitment.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Mattering was also reported to be the protective factor against depression symptoms and suicide ideation among young adults [22], [23]. The decision to involve mattering as our main predictor in this current study is also confirmed because it has been established that employees with higher levels of mattering tend to have higher job satisfaction, perceive lower job stress, as well as perceive higher work-life balance [4], [24], [25] that will lead to lower turnover intention [26]. Our second choice as the predictor of turnover intention was the organizational commitment.…”
Section: Introductionsupporting
confidence: 74%
“…It is important to note, however, that turnover intention does not always come hand-to-hand with the actual turnover; turnover intention is significantly predicted by poor mental health at work, such as stressful situation, while the actual turnover is predicted by the source of the stress, such as workload or social treatment [26]. In the context of our study, turnover intention was promoted by the entrepreneurial orientation, a variable that is considered controversial due to its impact on the job performance and turnover intention.…”
Section: Implicationmentioning
confidence: 99%
“…Continuing efforts for examining specific factors that improve the quality of care through empirical research is important. In this study, we focus on providers' job well-being and organizational support factors that have critical impacts on the community mental health workforce (e.g., Fukui et al, 2020).…”
mentioning
confidence: 99%
“…Community mental health organizations face many challenges that impede efforts to provide quality care, potentially attenuating public health impacts of treatment. Common problems in community mental health settings in the United States (US) include limited financial resources and short job tenure for clinicians (Dishop et al , 2019; Fukui et al , 2020; Glisson et al , 2006; Scanlan and Still, 2019). For the purposes of this study “clinician” is defined as any mental health service provider delivering services in public sector care.…”
Section: Introductionmentioning
confidence: 99%